Incidence of Medication Discrepancies and its Predicting Factors in Emergency Department - Morvarid ZARIF-YEGANEH; Mansoor RASTEGARPANAH; Gholamreza GARMAROUDI; Molouk HADJIBABAIE; Hojjat SHEIKH MOTAHAR VAHEDI (Tehran University of Medical Sciences, 2017)
Background: This study was conducted to evaluate the incidence of medication discrepancies and its related factors using medication reconciliation method in patients admitted to the emergency department of Tehran University of Medical Sciences hospitals. Methods: In this cross-sectional study, 200 adult patients with at least one chronic disease that used two regular prescription medications were included in 2015. After 24 h of admission, demographic data and patient's home medications were collected. Medication discrepancies were assessed through comparison of a best possible medication history list with the physician's orders. Results: Out of 200 patients (mean age, 61.5 yr; 86 males, 114 women), 77.5% of patients had one or more medication discrepancies. The most common discrepancies were medication omission (35.49%), change (14.22%) and substitution (10.97%), respectively. The relationship between number of comorbid conditions (P=0.025), regular home medications (P=<0.001), high-risk medications (P=0.032), medications pharmacological classes (P=<0.001) and medication discrepancies were statistically significant. Cardiovascular drugs compared to other medications classes showed the highest discrepancies (36.2%). Multiple logistic regression showed that the drug groups, including anti-infective for systemic use (OR=8.43; 95%CI 2.5-28.2; P=0.001), Antineoplastic and Immuno-modulator Agents (OR=0.49; 95%CI 0.27-0.87; P=0.016), Blood and Blood-Forming Organs (OR=0.33; 95%CI 0.21-0.52; P<0.001), Muscular-Skeletal System (OR=2.4; 95%CI 1.13-5.1; P=0.022), Nervous-System (OR=2.75; 95%CI 1.7-4.4; P<0.001), Respiratory-System (OR=0.38; 95%CI 0.22-0.67; P=0.001) were associated with the drug discrepancy. Conclusion: A medication discrepancy occurs commonly at hospital emergency department. Understanding the type and frequency of discrepancies with using structured medication reconciliation process can help clinicians to prevent them.